Rental VCD In D-NOS (Video-CD-Rental) Using Microsoft Visual Basic 6.0 - Rian Irawan; Diyah Ruri Irawati. SKom. MMSI (Jurnal Sistem Informasi, 2007)
Scientific research is aimed to bolster the performance of services and also to create a computerized reports using Microsoft Visual Basic 6.0. This research is a scientific research by collecting datum - datum in D - NOS (Video - CD - Rental). The author obtained data with  observations.  From  the  results  of  this  study  can  be  concluded  that  by  using  a computerized system that will facilitate and expedite the rental process - hiring and in making his report, when compared with the manual way.